Quasiconcavity of a separable product of utility functions. (2nd November 2018) - Berdi, Mohammed; Hassouni, Abdelhak
ABSTRACT: The nontrivial problem of the quasiconcavity of a separable sum of utility functions has been studied and solved by Debreu-Koopmans and Crouzeix-Lindberg via the introduction of convexity indices. This paper studies the equivalent problem of the quasiconcavity of a separable products. This approach makes the proofs easier.